Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T13:02:11+02:00
I liczba: x
II liczba: x+3
III liczba: x+2

x(x+3)(x+2)=-30
x^3+2x^2+3x^2+6x+30=0
x^3+5x^2+6x+30=0
x^2(x+5)+6(x+5)=0
(x^2+6)(x+5)=0

iloczyn dwóch liczb wynosi 0, gdy przynajmniej 1 z czynników wynosi 0, zatem:
x^2+6 = 0
x^2 = -6 sprzeczność

lub

x+5=0
x=-5

I liczba: x = -5
II liczba: x+3 = -2
III liczba: x+2 = -3
44 4 44
2010-04-14T13:09:31+02:00
A - x
b - x+3
c - x+3-1 = x+2

a*b*c = -30
x(x+3)(x+2) = -30
x(x²+2x+3x+6) = -30
x(x²+5x+6) = -30
x³+5x²+6x+30 = 0
x²(x+5)+6(x+5) = 0
(x²+6)(x+5) = 0
x = -5
x²+6 brak pierwiastków

a - x = -5
b - x+3 = -2
c - x+3-1 = x+2 = -3

(-5)*(-2)*(-3) = -30
39 4 39